KEKUATAN YURIDIS METERAI DALAM SURAT PERJANJIAN - Kusdi Wartanaya, Komang; A. Martana, Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013)
This paper entitled “Juridical Power of Seal on a Contract”. This paper usesnormative analytical methods and the statute approach. Validity of a contract shall beconsidered upon not only the presence of seal within it, but also upon the elementsstipulated in Article 1320 of Civil Code. Legal effects of seal shall be effective duringthe circumstances of dispute arise and as the means of evidence before the court. As theabsence of seal within a contract, shall not merely define a contract as null and void asa means of evidence before the court.
Keywords: Juridical Power, Seal, Contract